Panama canal expansion, U.S. trade diversion from west coast seaports and urban innovation - ChangKeun Park; JiYoung Park (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Adapting to the rapid process of globalization requires nodes of international trade and global financial operations conveyed in the world urban system. Urban and metropolitan areas need to strategically approach to incorporating the city economic activities to enlarge the scope and complexity of the city service and commodity. Because strong urban agglomerations usually lead to technological innovation, investigating the relation between the expansion of Panama Canal and its state and regional economic impacts that will be potentially affected within the U.S. can provides various policy insights in urban growth and technical innovations for the local areas. This study estimated reduced impacts of transportation and warehousing activities for foreign imports and exports for the west coast seaports of California, Oregon, and Washington as well as the concurrent impacts in other states stemming from the trade diversion in their direction, which will affect urban growth and innovation. We applied both the supply- and demand-side National Interstate Economic Models. We assumed that foreign imports and exports that currently arrive and leave the west coast customs district ports and are now transported to other U.S. Southern and East Coast states by truck and rail modes would be directly shipped to these other states via the deepened and expanded Panama Canal. The total negative impacts of transportation and warehousing values lost in the three west coast states from foreign import diversion were estimated to be 5795 million; for foreign exports, 1630 million. However, total positive gains due to the shift of transportation modes and new warehousing activities for foreign imports in the other states were estimated at 6304 million, while the gains were 9218 million for the case of foreign exports. The net impacts resulting from port modernization investment and shipping route changes will be an economic engine to affect U.S. states.
Keywords: 650; Panama canal expansion; Economic model; NIEMO; West coast seaports; Economic impacts